2022
DOI: 10.1136/jnis-2022-019295
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of wide-necked intracranial aneurysms using the Nautilus Intrasaccular System: initial case series of 41 patients at a single center

Abstract: BackgroundEndovascular treatment of intracranial wide-necked and bifurcation aneurysms (WNBA) is technically challenging. The Nautilus Intrasaccular System is designed to provide a mechanical barrier at the aneurysm neck to support coil embolization. We report the results of a single-center series of patients treated for intracranial aneurysms with the Nautilus.MethodsClinical and radiological data were retrospectively collected for all patients treated with the Nautilus for an unruptured or ruptured intracran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…If the mesh components protrude into the parent vessel, this poses a risk for thrombosis and antiplatelet medications are recommended [ 73 ]. A recent systematic review about WEB use in ruptured and unruptured aneurysms by Xie et al found 1/7 articles reported any antiplatelet use [ 75 ]. This review found thromboembolic complications to occur in 7% of the collected cases [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the mesh components protrude into the parent vessel, this poses a risk for thrombosis and antiplatelet medications are recommended [ 73 ]. A recent systematic review about WEB use in ruptured and unruptured aneurysms by Xie et al found 1/7 articles reported any antiplatelet use [ 75 ]. This review found thromboembolic complications to occur in 7% of the collected cases [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review about WEB use in ruptured and unruptured aneurysms by Xie et al found 1/7 articles reported any antiplatelet use [ 75 ]. This review found thromboembolic complications to occur in 7% of the collected cases [ 75 ]. The current study found 48 studies with 3583 cases that used an intrasaccular device for the management of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Giant aneurysms are uncommon and account for 7% of all these lesions ( 19 , 21 , 22 ). ICA bifurcation region aneurysms can be divided into wide-necked (neck width ≥4.0 mm or dome-to-neck ratio <2.0) and narrow-necked (neck width <4 mm, dome-to neck ratio >2) aneurysms ( 23 ). In addition, ICA bifurcation region aneurysms can be spontaneous, traumatic or secondary to radiation ( 24 , 25 ).…”
Section: Classifications Of Ica Bifurcation Region Aneurysmsmentioning
confidence: 99%